The Impact of Profitability, Liquidity, and Leverage on Firm Value with Dividend Policy as a Moderating Variable (A Study of Companies Listed on JII70, 2021-2024) : Impact of Profitability, Liquidity, and Leverage on Firm Value with Dividend Policy as a Moderating Variable (A Study of Companies Listed on JII70, 2021-2024) - Muhammad Rizqi Amrulloh; Muhammad Nanang Choiruddin (Universitas Indo Global Mandiri Palembang, 2026)
Objective: This research aims to empirically investigate the impact of profitability, liquidity, and leverage on firm value, and to broaden the understanding of the role of dividend policy as a moderating variable within the context of the Jakarta Islamic Index 70 (JII70). Design/Methods/Approach: This quantitative study analyzes companies listed on the JII70 at the Indonesia Stock Exchange over a four-year period from 2021 to 2024. Secondary data comprising annual financial reports were analyzed using Moderated Regression Analysis (MRA). Following a rigorous data trimming procedure to eliminate extreme outliers, the final validated sample consists of 106 observations. Findings: The empirical analysis demonstrates that the research model is highly fit, showing an Adjusted R Square of 43.7%. Profitability and leverage exert a significant positive effect on firm value, whereas liquidity shows no significant impact. The moderation test proves that dividend policy significantly dampens the effect of profitability on firm value, yet it does not moderate the effects of liquidity or leverage. Originality/Value: The novelty of this research lies in identifying the dampening effect of dividend policy on the profitability of Islamic companies during the post-pandemic recovery period. This study validates Signaling Theory by indicating that excessively high dividend payouts during economic recovery are perceived by the market as a signal of minimal future growth opportunities. Practical/Policy implication: These findings highlight the crucial need for corporate management to formulate dividend payout ratios carefully to avoid sacrificing future expansion prospects. For investors, this study serves as a practical guide for making investment decisions in the Islamic capital market by focusing on working capital resilience and expansion capabilities rather than solely on immediate dividend yields.